Function of Code Switching Performed by the EFL Teachers in Classroom Interaction - Andi Patmasari; Agussatriana Agussatriana (Hasanuddin University, 2019)
The objective of this research is to determine the functions of code switching performed by the EFL teachers in classroom interaction. This research used qualitative research design which was conducted in SMAN 1 Soppeng. The participants of this research were two English teachers of SMAN 1 Soppeng who were chosen by using purposive sampling technique. To collect the data, the researcher used two kinds of research instrument namely classroom observation and interview. The data obtained were analyzed through Miles and Huberman (1994) qualitative data analysis and combined it with discourse analysis. The procedure of data analysis divided into three stages, namely data reduction, data display, and conclusion drawing/verification. The result of data analysis indicated that there are eleven functions of code switching discovered during the teaching and learning process in classroom interaction, namely checking for understanding, lapses, grammar explanation, pronunciation practice, explaining the meaning of vocabulary, reiteration, topic switch, polite command, speech connective, interjection to get the students’ attention, and emphasize certain word or a point in the conversation. The functions may vary according to the context, situation, and the topic of the conversation.